Progress in microbial fuel cells for sustainable management of industrial effluents. (July 2021) - Tabassum, Nishat; Islam, Nafisa; Ahmed, Shoeb
Graphical abstract: Highlights: Versatility of the MFC technology for treatment of a variety of industrial wastes has been reviewed. Industries that can adopt the technology for waste management have been identified. Cost, scale-up and other performance issues discouraging MFC adoption in industrial settings have been discussed. Possible way forward for industries and for field deployment has been suggested. Choices of design and operational parameters depend on whether waste treatment or resource recovery is the target. Abstract: Microbial fuel cell (MFC) technology is a promising solution for both organic and inorganic effluent treatment, as it is capable of handling a variety of complex contaminants with simultaneous energy and resource recovery. Unlike conventional treatment technologies, MFCs can achieve removal of organic matter, persistent organic compounds, heavy metals and nutrients from categorically different waste effluents, while recovering energy and valuable substances. This makes the technology economically attractive, and viable for a wide range of industries for their waste treatment applications. However, in order to implement this technology as an on-site treatment unit, limitations pertaining to costs, scale-up and performance have to be addressed, with due emphasis on developing strategies that can be easily applied in industrial settings. This review summarizes the recent progress in the field of waste treatment and environmental remediation using MFCs, and examines these operational challenges. Cost-effective materials that have been implemented on the field and at large scales have also been highlighted. In addition, the review highlights the fact that there is a need to optimize the technology depending on energy or resource recovery. The MFC-based technology utilizes the synergy of bioremediation and bioelectricity production from wastes, offering a sustainable approach to industrial waste management.